Development of rapid advice guideline and standard and continuous updating guideline: experiences and practice - Jin, Ying-Hui (Mil Med Res, 2021)
We published rapid advice guidelines and updated guidelines for coronavirus disease 2019 (COVID-19) management on February 6, 2020, and September 4, 2020, respectively. These two guidelines vary widely in their developmental background, type of evidence, grade of recommendation and so on. We shared our experience for the development of these two guidelines to help clinical practitioners better understand and implement guidelines and to help guideline developers facilitate communication and discussion for guideline development during the pandemic.